Conceptual Design of Multi-agent System for Suramadu Bridge Structural Health Monitoring System - Seno Adi Putra; Bambang Riyanto; Agung Harsoyo; Achmad Imam Kistijantoro (Universitas Ahmad Dahlan, 2015)
Wireless Sensor Network (WSN) is small embedded devices deployed in large scale network with capability to sense, compute, and communicate. It combines modern sensor, microelectronic, computation, communication, and distributed processing technology. WSN has been taking an important contribution in structural health monitoring system, especially in Suramadu Bridge, one of the longest span bridges in Indonesia connecting Surabaya (East Java) and Madura Island. Due to subjected by environmental circumstance, it is necessary to implement intelligent and autonomous WSN to monitor the bridge condition, detect the bridge damage, and send warning message to bridge users when unsafe condition occurs. The multi-agent system is a promising approach to be implemented on intelligent and autonomous WSN, especially in the bridge structural health monitoring system. In this approach agents are empowered to have several intelligent learning capabilities for structural monitoring, damage detection, and prediction. This paper describes multi-agent system conceptual design that will be implemented as model of long span bridge structural health monitoring system considering system architecture and agent organization.